2011
DOI: 10.1038/nclimate1304
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of oxygen minimum zones may reduce available habitat for tropical pelagic fishes

Abstract: Habitat compression and associated potential habitat loss was validated using electronic tagging data from 47 blue marlin. This phenomenon increases vulnerability to surface fishing gear for billfishes and tunas 8,9 , and may be associated with a 10-50% worldwide decline of pelagic predator diversity 10 . Further expansion of the Atlantic OMZ along with overfishing may threaten the sustainability of these valuable pelagic fisheries and marine ecosystems.Dissolved oxygen is critical for sustaining most marine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
366
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(375 citation statements)
references
References 29 publications
8
366
1
Order By: Relevance
“…Some effects will be direct; for example, we expect alterations in the distributions and health of open-ocean and deep-sea fish populations and commercially exploited stocks. This impact will result from warming-induced changes in metabolism (Deutsch et al, 2015) and body size (Cheung et al, 2013) linked to latitudinal or depth shifts in species distributions, in addition to vertical habitat compression from OMZ expansions (Prince and Goodyear, 2006;Stramma et al, 2010Stramma et al, , 2012. Less clear are the impacts of acidification stress and multiple stressors on deep-sea fish populations and fisheries production (Rosa and Seibel, 2008).…”
Section: Implications Of Climate Forcing On Societal Uses and Values mentioning
confidence: 99%
See 3 more Smart Citations
“…Some effects will be direct; for example, we expect alterations in the distributions and health of open-ocean and deep-sea fish populations and commercially exploited stocks. This impact will result from warming-induced changes in metabolism (Deutsch et al, 2015) and body size (Cheung et al, 2013) linked to latitudinal or depth shifts in species distributions, in addition to vertical habitat compression from OMZ expansions (Prince and Goodyear, 2006;Stramma et al, 2010Stramma et al, , 2012. Less clear are the impacts of acidification stress and multiple stressors on deep-sea fish populations and fisheries production (Rosa and Seibel, 2008).…”
Section: Implications Of Climate Forcing On Societal Uses and Values mentioning
confidence: 99%
“…Though not resolved at the grid resolution shown in Figure 1, tropical and subtropical bathyal waters between 200 and 700 m, including those bathyal margins of all major eastern boundaries, have already lost considerable amounts of O 2 over the last half-century, and many OMZs have expanded in volume (Stramma et al, 2008(Stramma et al, , 2010(Stramma et al, , 2012Gilly et al, 2013;Deutsch et al, 2014). In the abyssal realm, seafloor habitats under areas of deep-water formation (e.g., those in the North Atlantic and Southern Oceans) could experience a maximum decline in O 2 concentration of 0.03 mL L -1 by 2100 (i.e., a 0.5% drop from current levels; Tables 2, 3; Figures 2, 3).…”
Section: Oxygenationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other oceanographic features have also been shown to affect the depth behavior of pelagic fishes. For example, Prince et al (2010) and Stramma et al (2012) demonstrated that the vertical distribution of sailfish and blue marlin was directly related to the amount of dissolved oxygen, which may act as a physical barrier to limit vertical movement (in the eastern Atlantic). However, considering the much higher concentrations of dissolved oxygen in the western Atlantic (Castro & Miranda, 1998;Braga & Niencheski, 2006), such influence is unlikely in the present case.…”
Section: Vertical Distributionmentioning
confidence: 99%